2020
DOI: 10.1073/pnas.1916065117
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate states of molecular self-assembly from liquid-cell electron microscopy

Abstract: Traditional single-molecule methods do not report whole-molecule kinetic conformations, and their adaptive shape changes during the process of self-assembly. Here, using graphene liquid-cell electron microscopy with electrons of low energy at low dose, we show that this approach resolves the time dependence of conformational adaptations of macromolecules for times up to minutes, the resolution determined by motion blurring, with DNA as the test case. Single-stranded DNA molecules are observed in real time as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 46 publications
1
73
0
Order By: Relevance
“…[21][22][23][24][25][26] Specifically, real-time monitoring by LCTEM has been shown to provide mechanistic information regarding morphological evolution in soft matter. 27,28 For example, Patterson and coworkers were able to observe the formation of vesicles from poly(ethylene oxide)-block-poly(ε-caprolactone) via a solvent-switch approach inside the liquid-cell transmission electron microscope. 29 Time-resolved in situ imaging revealed that vesicles were nucleated by liquid-liquid phase separation, specifically by polymer-rich liquid droplets in solution.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…[21][22][23][24][25][26] Specifically, real-time monitoring by LCTEM has been shown to provide mechanistic information regarding morphological evolution in soft matter. 27,28 For example, Patterson and coworkers were able to observe the formation of vesicles from poly(ethylene oxide)-block-poly(ε-caprolactone) via a solvent-switch approach inside the liquid-cell transmission electron microscope. 29 Time-resolved in situ imaging revealed that vesicles were nucleated by liquid-liquid phase separation, specifically by polymer-rich liquid droplets in solution.…”
Section: Progress and Potentialmentioning
confidence: 99%
“… 9 , 10 High-speed atomic force microscopy (AFM) enables the visualization of dynamic behavior during molecular self-assembly, however it has limited temporal resolution and has to be performed on surfaces, so is unsuitable for solution measurements. 11 Transmission electron microscopy (TEM), cryogenic (cryo-TEM) or liquid cell (LCTEM) transmission electron microscopy, can provide information about the structure and the morphology of the aggregates, 12 but the preparation of samples involves drying, staining, 13 or cryogenic vitrification steps 14 and the collection of images often leads to radiation damage to the sample. 15 , 16 In addition, these techniques require careful data interpretation, as well as availability of complex instrumentation.…”
mentioning
confidence: 99%
“…GLCs have also facilitated exciting research and findings in the field of nanoscience, such as crystallization and in situ crystal growth, [ 182 ] nucleation and shape formation of crystals, [ 183 ] study of molecular structure of water and ice, [ 184 ] lithium transfer in battery materials, [ 185 ] high‐resolution study of beam‐sensitive biological cells, [ 186 ] study of intermediate states during the self‐assembly of DNA double helices, [ 187 ] and exceptional spatial resolution study of nanocrystal etching on a single particle level. [ 188 ]…”
Section: Microscopy With a Graphene Substratementioning
confidence: 99%